Foucault e a filosofia: da crítica do mesmo à abertura para o outro - Leal, Guilherme de Freitas (2022)
The thesis aims to collaborate in understanding the relationship between Foucault and philosophy. Glimpsing the tripartite field of philosophy observed to occur post-Kant, Foucault calls this moment philosophical modernity precisely because the infinite as foundation leaves the scene and finitude starts to sustain itself. Crossing the critical project — the Critique of Pure Reason, the Critique of Practical Reason, and the Faculty of Judgment — with Anthropological Reflection, Foucault absorbs the philosophical tradition through Kant, concatenating, in addition, in Nietzsche a radical answer that will allow him to build his own thought analytics. Foucault observes that the source, the limit, and the extent of knowing, doing, and hoping reside between truth and freedom, concluding that man makes himself in the course of his history, in the interaction of his language, and in the use of his bios. Foucault's analyses constitute a Critique of the Same that necessarily consolidates itself into an Opening to the Other. In other words, by doing the Critique of the Same, that is, by delimiting the formations of knowledge, by establishing the limits of power relations, by fixing the possibilities of the practices of the self, one can promote Openness to Other ways of being, one can construct other discursive forms, other power relations, other subjectivities. In this sense, archeology, genealogy, and hermeneutics are read as methodological tools used by Foucault to perform this Critical determination of what is the Same of a certain time and place in order to finally make us think about the Opening to the Other. Literature and language are seen as knowledge Other, painting, engraving, photography, cinema, and theater as power Other, and the aesthetics of the self together with politics are seen as expecting Other. Experiences that manage to go beyond the Same and establish in the spheres of Knowledge, Power, and Self, the unheard of, what was never there before, neither as a source, nor as a limit, nor as an extension of theoretical, practical, or moral knowledge in the establishment of man's way of being. In this way, making possible an experience beyond man's being